Correlation Between Perfusion Abnormalities Extent in Ventilation/Perfusion SPECT/CT with Hemodynamic Parameters in Patients with Chronic Thromboembolic Pulmonary Hypertension - YILDIZELİ, BEDRETTİN; ÖZGÜVEN, SALİH (GALENOS YAYINCILIK, 2021)
Objectives: Chronic thromboembolic pulmonary hypertension (CTEPH) is a type of pulmonary hypertension with persistent pulmonary vascular obstruction and exercise intolerance, which may benefit from pulmonary endarterectomy (PEA). Ventilation/perfusion (V/Q) scan is the preferred screening test of CTEPH, which can be used to assess the anatomical extent of the disease. This study aimed to analyze the correlation between the extent of mismatched Q defects in V/Q single photon emission computed tomography/computed tomography (SPECT/CT) with preoperative clinical and hemodynamic parameters in patients with CTEPH. Methods: A total of 102 patients with CTEPH prior to PEA having V/Q SPECT/CT scans were retrospectively reviewed. Age, gender, New York Heart Association classification, intraoperative right-sided heart catheterization (mPAP and PVR), and 6-minute walk test (6MWT) findings were obtained from clinical records of patients. Results: Linear regression analysis showed a significant but weak correlation between the preoperative mPAP and PVR with the extent of mismatched Q defects in V/Q SPECT/CT (rs=0.09474 with p=0.0016 and rs=0.045 with p=0.045, respectively). No significant correlation was found between 6MWT and extent of mismatched Q defects in V/Q SPECT/CT (p>0.05). Conclusion: A quantitative assessment of Q defects on V/Q SPECT/CT might provide information about hemodynamic parameters in patients with CTEPH.
Keywords: Chronic thromboembolic pulmonary hypertension; ventilation/perfusion scintigraphy; mean pulmonary arterial pressure; pulmonary vascular resistance; 6-minute walk distance; ENDARTERECTOMY; MORTALITY; OUTCOMES; CT